Immunological potential of cytotoxic T lymphocyte antigen 4 immunoglobulin in murine autoimmune cholangitis. (15th May 2015) - Tanaka, H.; Yang, G‐X.; Tomiyama, T.; Tsuneyama, K.; Zhang, W.; Leung, P. S. C.; Coppel, R. L.; Joh, T.; Nadler, S. G.; Ansari, A. A.; Bowlus, C.; Gershwin, M. E.
Summary Cytotoxic T lymphocyte antigen 4 (CTLA‐4) immunoglobulin (Ig) is an important regulator of T cell activation and a fusion protein directed at CD80 and CD86; it blocks co‐stimulatory signalling and T cell activation. We have taken advantage of a murine model of human primary biliary cirrhosis (PBC), mice expressing a transforming growth factor (TGF)‐β receptor II dominant negative (dnTGF‐βRII) transgene to address the potential therapeutic efficacy of CTLA‐4 Ig. To mimic patients with PBC at different stages or duration of disease, we treated mice with either CTLA‐4 Ig or control IgG three times weekly from 3 to 12 or 24 weeks of age, or from 12 to 24 weeks of age. CTLA‐4 Ig treatment from 3 weeks of age significantly reduced liver inflammation to 12 weeks of age. Treatment initiated at 12 weeks of age also ameliorated the autoimmune cholangitis at 24 weeks of age. However, in mice treated at 3 weeks of age, suppression of liver inflammation was not sustained and colitis was aggravated when treatment was extended to 24 weeks of age. Our data indicate that, in dnTGF‐βRII mice, CTLA‐4 Ig treatment has short‐term beneficial effects on autoimmune cholangitis, but the effect varies according to duration of treatment and the time in which therapy was initiated. Further dissection of the events that lead to the reduction in therapeutic effectiveness of CTLA‐4 Ig will be critical to determining whether such efforts can be applied to human PBC.